PLATFORM UJIAN PILIHAN MAHASISWA SELAMA PEMBELAJARAN JARAK JAUH - Elmanora; Oktaviani, Maya; Zulfa, Vania (Jurnal Pendidikan Teknik dan Vokasional, 2022)
As an effort to break the chain of spreading Covid-19, the campus is implementing Distance Learning activities. There are many things that educators must prepare in carrying out distance learning activities, one of which is a platform for conducting exams. This study aims to analyze the exam platforms that are chosen by undergraduate students during Distance Learning activities. This research is quantitative descriptive. This study involved 119 students who were randomly selected. The research data was collected using Google Form. The data that has been collected were analyzed using descriptive analysis. The results showed that students chose Quizizz as a fun exam platform during Distance Learning activities. The reason is that students consider Quizizz to have an attractive design, easy to access, fun and challenging, and provide information about the results obtained and feedback. Thus, Quizizz can be an alternative choice for lecturers in giving exams to students, especially in Distance Learning activities.